Pengaruh Work-Life Balance dan Burnout terhadap Motivasi Kerja Karyawan Generasi Z (Studi Pada PT Gudang Baru Berkah) - Miftakhul Ulum; Sinollah Sinollah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
The purpose of this study is to examine the impact of work-life balance and burnout on the work motivation of Generation Z employees at PT Gudang Baru Berkah, both partially and simultaneously. This research employs a quantitative approach with 100 respondents. Data was collected through questionnaires and interviews, and analyzed using SPSS version 26. The results show that work-life balance has a positive and significant effect on work motivation, while burnout does not have a significant impact. When analyzed together, both variables have a significant positive influence on work motivation, accounting for 38.9% of the variance, while other unexamined factors also contribute. The limitation of this study lies in the small sample size. This research provides valuable insights into the factors affecting the work motivation of Generation Z employees in a corporate setting.